ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SMP BERDASARKAN GENDER DAN SELF CONCEPT - Dinny Novianti Azhari; Tina Rosyana; Heris Hendriana (IKIP Siliwangi, 2018)
Mathematical communication is the ability to express ideas or mathematical ideas both orally and in writing. Success in learning mathematics influenced cognitive aspects such as mathematical ability, affective aspects such as self concept, and gender differences. The method in this research using quantitative approach with the method correlational which aims to know the influence of gender and self concept towards the achievement of mathematical communication of junior high school students in the matter of building a rectangular flat. The population of this study is all students of class VII in one of the State Junior High School in West Bandung with selected sample of 11 female students and 16 male students. The instrument used consisted of a test of mathematical communication skills in the form of a description consisting of seven items and non-test instruments consisting of 10 positive statements and 10 negative statements of self concept. The result of this research shows that gender differences influence to students' mathematical communication ability. Female students are more dominant in terms of cognitive and answer math problems in writing with complete than male students. In addition, students' mathematical communication skills are not influenced by self concept.